A systematic review into expert knowledge elicitation methods for emerging food and feed risk identification. (June 2022) - Hadjigeorgiou, E.; Clark, B.; Simpson, E.; Coles, D.; Comber, R.; Fischer, A.R.H.; Meijer, N.; Marvin, H.J.P.; Frewer, L.J.
Abstract: An emerging risk results "… from a newly identified hazard to which a significant exposure may occur, or from an unexpected new or increased significant exposure and/or susceptibility to a known hazard ". In the field of emerging food and feed risks, expert knowledge elicitation methodologies represent important tools for identifying and addressing data gaps associated with emerging risk identification, particularly under conditions of risk uncertainty and/or ambiguity. A systematic review was conducted to identify expert knowledge elicitation methods which have been used in the context of emerging food and feed risks. The primary research questions were which existing expert knowledge elicitation methodologies have been used to study emerging food and feed risks? and what contexts or situations have been studied using expert knowledge elicitation methodologies in relation to emerging food and feed-related risks? Three databases were searched: Web of Science Core Collection, Scopus, and Google Scholar. Searches covered all studies published from 1998 onwards. A total of 59 studies were included in the review following the application of the inclusion and exclusion criteria. Given the heterogeneity of the included studies, a thematic analysis was applied to assess these papers in relation to the research questions. There was no one expert knowledge elicitation method consistently adopted for the identification of a specific type of emerging food and feed risk. Method triangulation was observed in 23 studies and was reported to improve the validity of results in 15 of these. Most published research considered emerging risks associated with societal controversy ("ambiguous risks"). Although the use of methodological triangulation appears to be helpful in relation to understanding emerging food and feed risks, future research into the development of a harmonised framework will enable the identification, processing, and evaluation of emerging food risks in a systemic way which can facilitate comparative analysis and harmonise mitigation strategies to address emerging risks and their drivers.